Self-Assembling Imageable Silk Hydrogels for the Focal Treatment of Osteosarcoma - Peng, Zhibin; Li, Ming; Wang, Yuan; Yang, Hongbo; Wei, Wei; Liang, Min; Shi, Jianhui; Liu, Ruixuan; Li, Rui; Zhang, Yubo; Liu, Jingsong; Shi, Xu; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: The standard treatment for osteosarcoma comprises complete surgical resection and neoadjuvant chemotherapy, which may cause serious side effects and partial or total limb loss. Therefore, to avoid the disadvantages of traditional treatment, we developed self-assembling imageable silk hydrogels for osteosarcoma. Methods: We analysed whether iodine induced apoptosis in MG-63 and Saos-2 cells by using CCK-8 and flow cytometry assays and transmission electron microscopy. Western blotting was used to analyse the pathway of iodine-induced apoptosis in osteosarcoma cells. PEG400, silk fibroin solution, polyvinylpyrrolidone iodine (PVP-I), and meglumine diatrizoate (MD) were mixed to produce an imageable hydrogel. A nude mouse model of osteosarcoma was estab-lished, and the hydrogel was injected locally into the interior of the osteosarcoma with X-ray guidance. The therapeutic effect and biosafety of the hydrogel were evaluated. Results: Iodine treatment at 18 µM and 20 µM for 12 h resulted in cell survival rate reduced to 50±2.1% and 50.5±2.7% for MG-63 and Sao-2 cells, respectively (P < 0.01). The proportion of apoptotic cells was significantly higher in the iodine-treatment group than in the control group (P<0.05), and apoptotic bodies were observed by transmission electron microscopy. Iodine could regulate the death receptor pathway and induce MG-63 and Saos-2 cell apoptosis. The hydrogels were simple to assemble, and gels could be formed within 38 min. A force of less than 50 N was required to inject the gels with a syringe. The hydrogels were readily loaded and led to sustained iodine release over 1 week. The osteosarcoma volume in the PEG-iodine-silk/MD hydrogel group was significantly smaller than that in the other three groups (P<0.001). Caspase-3 and poly (ADP-ribose) polymerase (PARP) expression levels were significantly higher in the PEG-iodine-silk/MD hydrogel group than in the other three groups (P<0.001). Haematoxylin and eosin (H&E) staining showed no abnormalities in the heart, liver, spleen, lung, kidney, pancreas or thyroid in any group. Conclusions: Self-assembling imageable silk hydrogels could be injected locally into osteo-sarcoma tissues with X-ray assistance. With the advantages of good biosafety, low systemic toxicity and minimal invasiveness, self-assembling imageable silk hydrogels provide a prom-ising approach for improving the locoregional control of osteosarcoma.